Ethnobotanical study of postpartum medicinal plants used by the Dayak Kalis in Nanga Danau, West Kalimantan, Indonesia - RUQIAH GANDA PUTRI PANJAITAN; KLAUDIA MARETA SANDRA; EKO SRI WAHYUNI; REXY MAULANA DWI KARMADI; KURNIA NINGSIH; TITIN TITIN; TRI HARSONO; SHOKHAN SHARIF ALI (Society for Indonesian Biodiversity, 2025)
Abstract. Panjaitan RGP, Sandra KM, Wahyuni ES, Karmadi RMD, Ningsih K, Titin, Harsono T, Ali SS. 2025. Ethnobotanical study of postpartum medicinal plants used by the Dayak Kalis in Nanga Danau, West Kalimantan, Indonesia. Biodiversitas 26: 5989-5999. The Dayak Kalis community in Nanga Danau Village, West Kalimantan, Indonesia, continues to rely on traditional medicine, particularly for postpartum care. However, no previous study has documented their specific practices. This research aimed to document medicinal plants used for postpartum treatment by the Dayak Kalis. Data were collected through interviews, observations, and documentation, and analyzed using Use Value (UV) and Frequency of Citation (FC). Three key informants (two traditional birth attendants and one customary elder) were selected purposively as knowledge holders. The study identified 10 species from 6 families, with the Zingiberaceae being the most dominant family. Leaves were the most frequently used plant part, typically prepared by boiling. Plants with the highest cultural importance included kunyit (Curcuma longa), daun tonton (Phyllanthus androgynus) and laia (Zingiber officinale), valued for cleansing the uterus, enhancing breast milk, and restoring stamina. Cross-cultural comparison revealed both similarities and variations in postpartum ethnomedicine across other Dayak Sub-ethnic Groups. These findings highlight the importance of documenting traditional knowledge to preserve biocultural heritage and support maternal health. Further phytochemical and pharmacological studies are recommended to validate efficacy and ensure sustainable use of these medicinal resources.